Diseño arquitectónico de Malecón inclusivo y multifuncional en el cantón Daule, parroquia La Aurora - Toledo Salinas, Josué Gustavo (2023)
The purpose of this architectural project is to address the lack of safeand accessible public spaces in the parish of La Aurora, canton Daule, inorder to improve the life and urban integration of its inhabitants. To achieve this goal, the project seeks to create an inclusive and multifunctional boardwalkthat provides architectural solutions to strengthen community life and promotesocial inclusion. The priority focuses on designing a waterfront that optimizes accessibility, strengthens community life and enhances the quality of life of the inhabitants. Affordable, multifunctional public spaces play an essential role in developinginclusive communities that share a sense of belonging and collaborationbyproviding recreational areas, fostering social interaction, and promotingtheoverall well-being of citizens...........